Badanie przedprocesowe czyli duszpasterskie, w świetle motu proprio „Mitis Iudex Dominus Iesus” - Pawlak, Tomasz (Ius Matrimoniale, 2017)
The amendment to the process to declare the nullity of marriage introduced a new institution, a pre-judicial or a pastoral inquiry. The purpose of this procedure is to help those who have experienced the drama of breaking up a sacramental marriage. The diocesan bishop and the parish priest are responsible for helping such persons. An inquiry should be entrusted to other persons who will be adequately prepared for this. A pre-judicial inquiry is intended to be a tool to help assess the situation of such persons in order to determine the legitimacy case to present petition to the competent tribunal. Faithfull in the pastoral inquiry should be acquainted with the procedure and should help them to prepare formally to start process to declare the nullity of marriage. Some situations do not qualify for declaring the nullity of marriage. Then the pastoral inquiry should help those who have experienced the breakup of marriage to point out other forms of help that will service them to find the role, the meaning, and the function in the community of the Church. For this reason, the ecclesiastical law obliged those responsible for carrying out this procedure to cooperate with other legal entity who have the possibility to provide adequate assistance within the framework of structures of pastoral care of marriage.